Estrategias heurísticas y competencia matemática en los estudiantes de secundaria de la Institución Educativa CRFA Santa Teresa Primera Zona 2024 - Vargas Bermudez, Ossel (2025)
The objective of this study was to determine the relationship between heuristic strategies and mathematical competence among secondary school students at IE CRFA Santa Teresa - First Zone 2024. To this end, a quantitative, correlational approach was applied, with a non-experimental design and a sample of 33 students (no sampling was conducted; the entire secondary school population of the educational institution under study was included). The instrument used to measure variable 1: Heuristic Strategies was an ordinal Likert scale, while for variable 2, the grades recorded by the teacher during the term covered by the research were used. Content validity of the instruments was assessed by three experts, resulting in a finding that the instruments applied were appropriate, with an average value of 91.3. For the application of the instruments, parents were consulted and signed an informed consent document. Likewise, reliability for internal validity was assessed, yielding a Cronbach’s alpha value. The results obtained: p-value<0,001 <α=0,05; with a Spearman’s Rho correlation coefficient of 0,739 (appropriate for finding relationships between ordinal data), indicated the existence of a significant, positive, and strong relationship between heuristic strategies and performance in mathematical competence. This finding suggests that the regular use of heuristic strategies is associated with the development of mathematical competence among the students considered in the study.